2016
DOI: 10.1136/jnnp-2015-312600
|View full text |Cite
|
Sign up to set email alerts
|

Back on the scent: the olfactory system in CNS demyelinating diseases

Abstract: Olfactory dysfunction is recognised across an ever broadening spectrum of neuropsychiatric conditions including central nervous system (CNS) demyelinating diseases such as multiple sclerosis (MS) and neuromyelitis optica (NMO). In this review, we unravel the striking evidence highlighting how olfactory loss is a common clinical feature in MS and NMO. We provide an overview of the supportive psychophysical, electrophysiological, radiological and pathological data that point to the anatomical substrate of olfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 64 publications
(143 reference statements)
1
25
0
Order By: Relevance
“…One scent molecule may bind to different receptors with varying affinities and activate several receptors at once, forming a complex scent fingerprint [ 2,3 ] that is carried to the central nervous system (CNS) for analysis ( Figure a). [ 4–6 ] It is this integration of olfactory receptor combinatorics with CNS pattern recognition that allows the olfactory system to discriminate scents so efficiently.…”
Section: Figurementioning
confidence: 99%
“…One scent molecule may bind to different receptors with varying affinities and activate several receptors at once, forming a complex scent fingerprint [ 2,3 ] that is carried to the central nervous system (CNS) for analysis ( Figure a). [ 4–6 ] It is this integration of olfactory receptor combinatorics with CNS pattern recognition that allows the olfactory system to discriminate scents so efficiently.…”
Section: Figurementioning
confidence: 99%
“…In the 1980s, a link between chronic sinusitis and MS relapses was established by Derek Gay, in the absence of any isolated pathogen, which is especially pertinent in light of newer ‘nose-to-brain’ hypotheses of MS aetiology 47. Further longitudinal studies have shown a correlation between clinical systemic infection and MS relapses.…”
Section: Environmental Influencesmentioning
confidence: 99%
“…The present evidence revealed that the mean incidence of olfactory function in MS patients was 11-50% (average: 35.6%) through psychophysical methods. 10 Several commonly used olfactory evaluation methods include the Sniffin' Sticks test, University of Pennsylvania Smell Identification Test, simplified odor Identification test, T/T olfactory meter test, and Connecticut Chemical sensory Clinical Research Center olfactory test among the category. Of note, the results differ in nature and extent with different methods.…”
Section: Introductionmentioning
confidence: 99%